What pacing strategy 800 m and 1500 m swimmers use? - Tolomeu de Oliveira, G.; Werneck, F. Z.; Coelho, E. F.; de Moura Simim, M. A.; Macedo Penna, E.; Melo Ferreira, R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2019)
Pacing strategy (PS) has a decisive impact on performance, especially on long-term races. The objective of this study is to characterize the PS used in swimming races of 800m and 1500m freestyle by the finalists of the Olympic trials of the United States, Europe and Brazil, and the Olympic finalists of 2016. Time partials of 63 athletes were analyzed using a decision tree and the CHAID method. The results showed that parabolic was adopted by swimmers of 800m, they start in first lap (29.67 ± 0.88 s), followed by an increase in time (+1.77 s) and a subsequent increase in time (32.04 ± 0.89 s), at the end, the swimmers presented an acceleration, reducing the average of the to 31.44 s. And by the free 1500m swimmers, divided into blocks with a faster average start (29.25 ± 1.15 s), half of the slowest race (30.30 ± 0.76 s), and a new acceleration at the end of the event (29.92 ± 1.12 s), both in the selective Olympic Games and the 2016 and 2016 Olympic final. The worst partials times were observed in the Brazilian Selective (Test Event) (31.11 ± 0.78 s). Medalist, despite presetting the same OS, can sustain a better rhythm throughout he 800m (31.52 ± 1.03 s) and 1500-m (29.80 ± 0.78). We conclude that parabolic PS is the optimal strategy adopted by swimmers of 800-m and 1500m freestyle.